On boredom, faith and nihilism - Šerpytytė, Rita (Religija ir kultūra, 2008)
The article focuses anew to the question „What is a Boredom?“. By using different theoretical and „common sense“ approaches, the relationship between a Boredom and Melancholy as problematic one is being disclosed. The certain metamorphosis of Boredom – its converting or changing to Melancholy – expresses the crucial aspects of „ontology“ of a Boredom. By interpreting not only the theoretical attitudes, but also the works of art, the author reveals the relationship of a Boredom with Faith and religion as being actualized.
Keywords: boredom; melancholy; nihilism; faith